The energy relay: a proofreading scheme based on dynamic cooperativity and lacking all characteristic symptoms of kinetic proofreading in DNA replication and protein synthesis. - Hopfield, J J (1980)
A mechanism for proofreading biosynthetic processes requiring high accuracy is described. The previously understood "kinetic proofreading" mechanism of enhancing accuracy has distinguishing characteristics such as the non-stoichiometric use of substrate or cosubstrate that have allowed its identification in aspects of DNA and protein synthesis. The proofreading scheme developed here, though generically related, lacks all the previous identifying features. A DNA polymerase proofreading in this manner need neither generate dNMP nor have a 3' leads to 5' exonuclease activity. Protein synthesis could be proofread even with stoichiometric GTP consumption or without elongation factor Tu . GTP. The kinetic scheme that generates this proofreading makes use of an "energy relay" from previous substrate molecules and is a representative of a class of nonequilibrium processes displaying dynamic cooperativity. This proofreading mechanism has its own identifying characteristics, which are sufficiently subtle that they would have generally escaped notice or defied interpretation.